Downregulation of the microRNA biogenesis components and its association with poor prognosis in hepatocellular carcinoma. Issue 5 (20th March 2013) - Kitagawa, Noriyuki; Ojima, Hidenori; Shirakihara, Takuya; Shimizu, Hiroko; Kokubu, Akiko; Urushidate, Tomoko; Totoki, Yasushi; Kosuge, Tomoo; Miyagawa, Shinichi; Shibata, Tatsuhiro
<x xml:space="preserve">Abstract</x> Genetic alterations and deregulation of the miRNA biogenesis pathway components have been reported in human tumors. Tissue‐specific deletion of the Dicer gene, which encodes an essential miRNA processing enzyme, promotes carcinogenesis in animal models. These features indicate that aberrant miRNA biogenesis components are directly associated with cancer. For the present study, we conducted quantitative RT‐PCR of 14 genes that are related to the miRNA biogenesis pathway in 47 paired samples of primary hepatocellular carcinoma (HCC) and matched non‐cancerous liver. Expression of seven genes (Dgcr8, p68, p72, Dicer, Ago3, Ago4 and Piwil4) was significantly decreased in primary HCC, especially in non‐viral HCC subtypes, compared to the non‐cancerous liver. Combinations of decreased expression of the miRNA biogenesis components in non‐cancerous liver were related to cigarette smoking, alcohol intake and diabetes, which are known to be risk factors for HCC, and were also associated with the occurrence of multicentric tumors. Reduction of two of these genes (Dicer and p68) in HCC was associated with poor prognosis. Trimethylation of histone H3 lysine 27 in the promoters is implicated in the deregulation of these miRNA‐biogenesis‐related genes in non‐HBV genome integrated HCC cell lines. In conclusion, deregulation of the miRNA biogenesis pathway components is frequently observed in non‐viral‐associated HCC and is linked to etiological risk factors and poor prognosis. Our study further showed that epigenetic regulation could be implicated in the deregulation of these genes during hepatocarcinogenesis.